The standard of proof “beyond a reasonable doubt” in criminal proceedings of Ukraine in the context of the ECHR case-law - Ковальчук, Сергій Олександрович; Ковальчук, С. О.; Ковальчук, Сергей Александрович; Kovalchuk, Serhii O.; Дроздов, Олександр Михайлович; Дроздов, О. М.; Дроздов, Александр Михайлович; Drozdov, Oleksandr M.; Гринюк, Володимир Олексійович; Гринюк, В. О.; Гринюк, Владимир Алексеевич; Hryniuk, Volodymyr O.; et al. (Editorial Primmate S. A. S., 2021)
The purpose of the paper is to determine a content of the standard of proof “beyond a reasonable doubt” (SP “BRD”) in the ECHRcase law and Ukrainian criminal proceedings by defining the criteria that characterize it. The subject is the SP “BRD”, doctrine of Ukraine and case-law, including its criticism by the individual judges of the ECHR and Ukrainian scholars. The research methodology includes the methods of analysis, the method of synthesis, the methods of deduction and induction, comparative-legal method, systematic and formal-legal methods. The results of the study. The acceptability of the SP “BRD” in the Ukrainian criminal proceedings is substantiated, in particular, its compliance with the purpose of criminal procedural proof. Practical implication. The criteria which characterize the SP “BRD” in the ECHR’s and SC’s case law are highlighted.

Метою статті є визначення змісту стандарту доказування «поза розумним сумнівом» (СД «ПЗС») у судовій практиці Європейського суду з прав людини та в кримінальному провадженні України шляхом визначення критеріїв, які його характеризують. Предметом дослідження є аналіз СД «ПЗС» у судовій практиці ЄСПЛ, українському кримінально -процесуальному законодавстві, доктрині України та судовій практиці, включаючи критику окремих суддів ЄСПЛ та українських науковців. Методологія дослідження включає метод аналізу, метод синтезу, методи дедукції та індукції, порівняльно-правовий, системний та формально-правовий методи. Результати дослідження. Обґрунтовано прийнятність СД «ПЗС» у кримінальному провадженні в Україні, зокрема, визначено його відповідність меті кримінально-процесуального доказування. Практичний підтекст. Висвітлено критерії, які характеризують СД «ПЗС» у судовій практиці ЄCПЛ та ВС.
Drozdov O. The standard of proof “beyond a reasonable doubt” in criminal proceedings of Ukraine in the context of the ECHR case-law / O. Drozdov, V. Hryniuk, S. Kovalchuk, L. Korytko, G. Kret // Amazonia Investiga. – Vol. 10. – Iss. 46. – Editorial Primmate S. A. S., 2021. – P. 281-289.
Keywords: standards of proof; beyond a reasonable doubt; burden of proof; criminal proceedings; ECHR; стандарти доказування; поза розумним сумнівом; тягар доказування; кримінальне провадження; Європейський суд з прав людини; Research Subject Categories::LAW/JURISPRUDENCE